Finally a really forensic worldwide standard: ISO 21043 Forensic sciences, Part 4, Interpretation - Charles E.H. Berger (Forensic Science International: Synergy)
Many influential reports have highlighted the need for improvement in forensic science, calling for a better scientific foundation and quality management. A well-structured and internationally agreed-upon framework is provided by the ISO 21043 Forensic sciences standard series, the importance of which goes beyond traditional quality management. Guided by principles such as logic, transparency, and relevance, the ISO 21043-4 Interpretation standard contains requirements and recommendations, but also introduces a common language and supports both evaluative and investigative interpretation. Development of the standard aimed for the flexibility needed across diverse areas of expertise while promoting consistency and accountability, and this paper explains the standard and the principles that underpin it from an insider perspective.Above all, ISO 21043 represents a unique opportunity to unify and advance forensic science as a discipline, and to improve the reliability of expert opinions and trust in the justice system.